Optimization Parameters for Enzymatic Clarification of Dragon Fruit Juice - N. P. Minh (Journal of Global Pharma Technology, 2019)
Fresh dragon fruit juice has high viscosity and turbidity. Fruit juice clarification by ultrafiltration only does not remove active haze precursors, allowing haze formation during storage. Pectinase treatment can resolve this matter. Pectinase can break down complex polysaccharides of plant tissues into simpler molecules like galacturonic acids. Pitaya or dragon fruit can be utilized to produce fruit juice as functional beverage. In our research, pectinase was used in different parameters of enzyme concentration (0.02, 0.04, 0.06, 0.08, 0.10%), temperature (30, 35, 40, 45, 50oC), time (45, 60, 75, 90, 105 min) and pH (4.2, 4.4, 4.6, 4.8, 5.0). Total soluble solid (oBrix), total phenolic (g/L), turbidity (NTU) and viscosity (cP) were important indicators to identify the optimal treatment. Our results showed dragon fruit juice would have the best total soluble solid, total phenolic, clarity as well as viscosity by treatment of pectinase concentration 0.08%, temperature 40oC in 90 min at pH 4.6. Our finding concluded that pectinase treatment would be a potential efficient approach of cloud removal in dragon fruit juice productionKeywords: Pectinase, Dragon fruit, Total soluble solid, Phenolic, Turbidity, Viscosity.